Lymph node metastasis outside of a tumor-bearing lobe in primary lung cancer and the status of interlobar fissures: The necessity for removing lymph nodes from an adjacent lobe. Issue 12 (March 2019) - Li, Hui; Wang, Ruimin; Zhang, Dexian; Zhang, Yongming; Li, Wanhu; Zhang, Baijiang; Liu, Qi; Du, Jiajun
Abstract : Abstract: The new Tumor Node Metastasis staging system does not recognize fissure status with respect to adjacent lobe invasion (ALI) in lung cancer. Furthermore, no specific surgical strategies have been recommended for lymph node dissections around adjacent nontumor-bearing lobes (NTBLs) according to fissure status. Therefore, this study was undertaken to investigate the necessity of removing additional adjacent lobe lymph nodes in patients with nonsmall cell lung cancer (NSCLC) for lesions limited to in the vicinity of the interlobar fissure. From August 2013 to March 2015, the records of 332 patients, who underwent systematic mediastinal lymph node dissection, were reviewed in this retrospective study. The bronchial lymph nodes had been subjected to pathological examination, and the status of the fissures was also recorded. A statistical analysis was performed to identify the significant predictors of lymph node metastasis. The patients were divided into a nonadjacent lobe invasion (NALI) group (n = 295) and an ALI group (n = 37). There was a significant difference in tumors with pN2 disease between the ALI and NALI groups (37.8% vs 8.8%, P  = .001). ALI tumors had significantly more frequent pleural involvement than NALI tumors (62.2% vs 43.1%, P  = .035). The frequency of N2 involvement among tumors invading across the complete fissure was higher than that of the tumors invading across the incomplete fissure (44.4% vs 14.3%, P  = .015). However, the frequency of N1 involvement among tumors invading across the incomplete fissure was not statistically different than that of tumors not invading across incomplete fissure (32.1% vs 24.2%, P  = .357). Regarding lymph node metastasis in NTBL, 15 (12.7%) patients had lymph node metastases in NTBLs. Pleural involvement was an independent predictor of lymph node metastasis in an NTBL. A greater frequency of N2 lymph nodes existed in NSCLC with invading adjacent lobe across complete fissure, extensive lymphatic resection within the hilum, and NTBL in tumors with pleural involvement are justifiable and necessary.